Peningkatan Hasil Belajar IPA melalui Model Pembelajaran Kooperatif Tipe NHT pada Siswa Kelas VIII di SMP Perintis Bersama Sejahtera Medan Tahun Pelajaran 2023/2024 - Nani Sri Rezeki; Andre Agachi Purba; Ika Trisni Simangunsong (Journal on Education, 2024)
This research aims to improve science learning outcomes for class VIII students at Perintis Bersama Sejahtera (PBS) Medan Middle School through the implementation of the NHT Type Cooperative Learning Form. The research method used is Classroom Action Research (PTK). The research sample consisted of 16 male students and 13 female students in class VIII at SMP PBS Medan. Information is collected through monitoring (observation) and tests, after which the information is analyzed using quantitative descriptive methods. The research results show that in general the average learning outcomes in the pre-cycle reached 54.13, increased in cycle I to 80.25, and reached maximum results in cycle II with an average of 95.25. The percentage level of learning completion in the pre-cycle only reached 20%, increased in cycle I to 55.35%, and reached 95% in cycle II.